The Impact of the Work Environment on the Performance of Paramedics in the Saudi Red Crescent Authority in the Makkah Region - Yassir Mohammed Eid Almabadi; Nawaf Omar Eidha Alsalmi; Rakan Ajmi Ghalib Almutairi; Wael Alofain Hamidan Alsahafi; Yasir Hassan Mufareh Alzhrani; Foad Mohamad Saliman Al-Ogmani; Nawaf Mohammed Aown Alabdali; Mansour Abdullah H Altarjami; Ali Aeish A Alsulami; Baraa Abdulrazaq Mohammed Abu Ruzayzah; Hesham Abbad Obidullah Allehyani; Mazen Abdulrahman Almutairi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study aimed to investigate The Impact of the Work Environment on the Performance of Paramedics in the Saudi Red Crescent Authority in the Makkah Region.The research utilized a descriptive analytical methodology to achieve its objectives. The study population comprised all employees of the Saudi Red Crescent Authority in the Makkah region. The sample included 186 paramedics (technicians, emergency specialists, and administrators). A questionnaire was used as the data collection tool. Based on the findings, the study identified several key results. There is positive strong significant relationship between the training dimension of the work environment and the performance of paramedics working for the Saudi Red Crescent Authority in the Makkah region. There is positive moderate significant relationship between (incentives - technological empowerment - nature of work conditions - participation in decision-making) dimensions of the work environment and the performance of paramedics working for the Saudi Red Crescent Authority in the Makkah region. For (Training - Incentives - Technological Empowerment - Nature Working Conditions - Participation Decision Making) there are no significant difference in the responses according to educational level, job title, years of experience. In light of these results, the study recommends:Implement a comprehensive training and development program to ensure paramedics stay updated with the latest medical advancements, emergency response techniques, and equipment usage.Incorporate simulation-based training exercises to provide paramedics with realistic scenarios and opportunities to practice their skills in a controlled environment.Ensure that paramedics receive fair and competitive compensation that reflects their level of responsibility, experience, and performance. Foster a culture of employee involvement by seeking input and feedback from paramedics on work processes, policies, and decision-making.